Re-evaluating Lady Gregory in modern Irish literature : a feminist ethics study - Chang, Tsung-chi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Women’s subordinate status in twentieth-century Irish literature has come under criticism in recent years. Irish women’s subjugation becomes apparent when we compare W. B. Yeats and Augusta Gregory. Whereas Yeats has been universally acknowledged in the past few decades as the spokesman of the Irish Literary Revival and an icon of modern Irish literature, Lady Gregory was ridiculed by George Bernard Shaw as the helping maid of the Abbey Theater. In this paper, a textual analysis of Lady Gregory’s plays is brought into discussion with Carol Gilligan’s and Nel Noddings’s feminist ethics to further explore the role women played in modern Irish literature. This paper aims at clarifying the nature of female writing as exemplified in Lady Gregory’s works. Unlike traditional studies on Lady Gregory and her plays, which focus on women’s subjugation in the male-dominated Irish society around the early twentieth century, the main findings of this research help shed new lights on the value of women in Gregory’s plays via an ethical feminist approach. The implication of this study is that women, who are apparently disempowered in traditional male-oriented moral thinking, are much more valuable and powerful when they are evaluated from ethical feminism.